Date night [videorecording (DVD)] - Carell, Steve, 1962-; Fey, Tina, 1970-; Henson, Taraji P.; Simpson, Jimmi; Common (Musician); Fichtner, William; Meester, Leighton, 1986-; Wahlberg, Mark, 1971-; Wiig, Kristen, 1973-; Ruffalo, Mark; Kunis, Mila, 1983- (20th Century Fox Home Entertainment, 2010)
An ordinary couple is in the right place, on the wrong night. Phil and Claire Foster are a sensible, suburban husband and wife slogging through their daily lives and marriage. But a case of mistaken identity sets off an outrageous chain of events involving small-time thieves, big-city mobsters, corrupt cops and a crazed cabbie, as the Fosters' 'date night' turns into a wild ride they'll never forget!